Factors Associated With Renal Involvement in Primary Sjögren's Syndrome: A Meta-Analysis - Hong, Ruping; Xu, Dong; Hsieh, Evelyn; Xiang, Yirong; Zhao, Jiuliang; Wang, Qian; Tian, Xinping; Li, Mengtao; Zhao, Yan; Zeng, Xiaofeng (Frontiers in Medicine, 2020)
Background: Renal impairment is a critical complication in primary Sjӧgren ’s syndrome (pSS), resulting in chronic renal disease and even death. This meta-analysis was designed to find out the relevant factors of renal involvement in pSS. Methods: PubMed, EMBASE, Cochrane Library, Scopus, and Web of Science were systemically searched by August 30, 2019. Studies were selected according to inclusion criteria, and data was extracted by two researchers independently. The Newcastle-Ottawa Scale was applied for quality assessment. Considering the existence of heterogeneity, we used a random-effects model in this meta-analysis. Meanwhile, a sensitivity analysis was conducted to investigate the cause of heterogeneity. Publication bias was showed in the funnel plot and evaluated by Begg’s and Egger’s tests further. Results: of 9989 articles identified, five articles enrolling 1867 pSS patients were included in the final analysis, 533 with and 1334 without renal involvement. There were no statistical significances in age and gender between these two groups. According to meta-analysis, anti-SSB antibody and arthralgia showed a significant association with renal involvement in pSS, the overall odds ratio (OR) values of which were 1.52 (95% CI, 1.17-1.97) and 0.58 (95% CI, 0.43-0.79), respectively. While the overall OR values of anti-SSA antibody, rheumatoid factor, dry eyes and labial salivary gland biopsy were just 0.90 (95% CI, 0.49-1.64), 1.05 (95% CI, 0.59-1.86), 0.60 (95% CI, 0.34-1.06), and 1.32 (95% CI, 0.86-2.02) separately. Conclusion: The presence of anti-SSB antibody is positively associated with renal involvement in pSS, while arthralgia is inversely associated. Large-scale prospective cohort studies are needed in the future to identify risk factors further.